Proses Legislasi dan Pelaksanaan Perda Wajib Belajar 12 Tahun di Kota Bukittinggi - Dwi Damayanti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Secondary education plays a crucial role in shaping students’ character and competencies as essential foundations to face global challenges. Although Bukittinggi City is renowned for its strong educational tradition, structural barriers such as economic disparities, limited infrastructure, and uneven distribution of educators remain significant challenges to ensuring inclusive and equitable education. In the context of regional autonomy, the role of the Regional House of Representatives (DPRD) is vital in formulating policies through regional regulations (Perda). This study aims to analyze the formulation and implementation process of Regional Regulation No. 7 of 2023 on the Twelve-Year Compulsory Education Program in Bukittinggi City. Using a descriptive qualitative approach, data were collected through in-depth interviews and document analysis. The findings reveal that the legislative process involved issue identification, academic draft preparation, discussions, and ratification, engaging multiple stakeholders. Early evaluations of implementation indicate a positive impact on cultural preservation through education, although challenges persist regarding the readiness of human resources and educational facilities. To enhance implementation, teacher capacity must be strengthened through training, culturally-based learning modules should be developed, and adequate funding and infrastructure must be provided. Furthermore, regular evaluation mechanisms and the involvement of traditional leaders are essential to ensure that this regulation genuinely addresses educational needs and reinforces the cultural identity of the younger generation.